Science Mapping of Perceived Organizational Support: A Bibliometric Analysis Approach - Pringgabayu, Dematria; Disman, Disman; Eeng Ahman (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
The purpose of this study is to obtain related topic and information regarding perceived organizational support. In conducting this study, the researcher utilized Scopus database for data mining and extraction. A total of 816 articles were discovered in the Scopus database accessed on July, 2023. Afterward, VOSviewer is utilized for scientific mapping and analysis of publication performance such as identify the contributions of authors, journals, countries, and author keywords number. Several countries have contributed to publications of perceived organizational support. The data reveals that the US contributes the most to this publishing subject, followed by China, India, the UK, Australia, Malaysia, Pakistan, South Korea, Canada, and Turkey. Most works on the topic are from these nations. The "International Journal of Human Resource Management" has the most important influence on this topic based on article document output. While, "Journal of Management" has the greatest number of citations.  This topic's top five authors write the most articles and Stinglhamber F. is the most prominent author in perceived organizational support study. Meanwhile, the most referenced author in this field is Eisenberger R., with 1,300 citations. This research can serve as a point of reference for future research pertaining to POS topic.